Handbook of research on managerial thinking in global business economics - Dinçer, Hasan, 1982-; Yuksel, Serhat, 1983- (Business Science Reference, 2018)
"This book identifies the importance of strategic decision making in competitive environment by analyzing the impacts of innovative managerial thinking on the global financial economics. It also covers topics such as strategic management, business planning, and risk management"--